"Concomitant" Cutaneous and Nodal Spitz Nevus/Tumor: A New Scenario for an Old Problem. (15th May 2022) - Ferrara, Gerardo; Lattanzi, Valeria; Leonardi, Elena; Broglia, Irene; Barbareschi, Mattia
Abstract: Spitz tumors are notoriously characterized by a high propensity to nodal involvement with a morphologically malignant (intraparenchymal) pattern but with little or no tendency toward further spread. We describe a case of spindle cell Spitz neoplasm removed from the thigh in a 34-year-old woman and initially diagnosed as "Spitzoid melanoma;" the sentinel node was characterized by a morphologically benign pattern of nodal involvement, with prevailingly capsular and septal aggregated of melanocytes showing the same cytomorphological features as the cutaneous tumor. Both the cutaneous and the nodal tumor were strongly ROS1-positive on immunohistochemistry; rearrangement of the ROS1 gene was confirmed with fluorescence in situ hybridization on the cutaneous tumor. The clonal relationship between the cutaneous and the nodal capsular/trabecular tumor, as established by their morphological and immunophenotypical resemblance, underlines the existence of a morphologically benign pattern of spread of Spitz neoplasms, as also suggested by the occurrence of eruptive Spitz nevi.